Utilization of Instagram Application as Personal Branding Dr. Richard Lee on Instagram Account @dr.richard_lee - Artamevia, Delly Puspita; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2024)
Social media provides a space for individuals to express themselves, build their self-image, and achieve personal and professional goals. One of the popular social media platforms is Instagram. Apart from being able to build a brand, the function of Instagram's presence can also build personal branding for individuals. Personal branding is the process of building a positive and distinctive self-image to achieve certain goals. For individuals themselves, personal branding can help them in various aspects of life, such as career, business, and social relationships. The existence of this research aims to analyze the use of the Instagram application as Dr Richard Lee's personal branding on the @dr.richard_lee Instagram account. Therefore, the problem formulation of this research is how the utilization of the Instagram application as Dr Richard Lee's personal branding on the @dr.richard_lee Instagram account. This research method uses descriptive qualitative with observation and documentation data collection techniques. This research uses purposive sampling technique, personal branding theory from McNally & Speak using 3 points, namely: a.) distinctiveness, b.) relevance, c.) consistency. Through these 3 points, it is easier for researchers to find out how the use of Instagram social media can affect the personal branding of Dr. Richard Lee. As a result of this research, it can be concluded that Dr. Richard Lee succeeded in doing the 3 main points in this personal branding theory on the Instagram platform. Through the features provided by Instagram, such as IGTV, Instagram stories, and Reels. Dr Richard Lee can strengthen and promote his self-image and be recognized internationally. Effective personal branding involves choosing distinctive characteristics, relevance, and consistency. Through effective personal branding, Dr. Richard Lee can create a positive self-image, build trust, and become an inspirational figure for the community.